“Net” value co-creation: The effect of interactions on consumer citizenship behavior in online travel communities - Guan, Biyu; Chen, Haiquan; Liu, Yunhao; Liu, Rui; Wu, Ailing (Frontiers in Psychology, 2022)
Online traveling community is initiated by companies but its survival is inextricably linked to consumer citizenship behaviour (e.g. out-group recommendation, in-group helping, and inward response). The majority of researches have investigated consumer behavior of brand community such as consumer satisfaction, brand loyalty and purchase intention. A few scholars try to explore consumer behaviors beyond the purchase, like participation, which was concerned as the value co-creation. However, value co-creation of the community should depend on consumers’ citizenship behaviors instead of their pure participation. Therefore, this study empirically examines consumer interaction, its effect on consumer psychology and citizenship behaviors of online travel community. The findings demonstrated that consumer interaction facilitated participants’ self-identity and their perceived social support, which enhanced their community identification and thus their citizenship behaviors. Furthermore, the motivations of participation have influence on this mechanism. Specifically, symbolic motivation moderates the relationship between consumer interaction and their self-identity; while utilitarian motivation moderates the effect of consumer interaction on their perceived social support. These findings contributed to the intervention of consumer citizenship behavior in online traveling community and provide insights for the management of online travel community from the perspective of value co-creation.